Шалый малый - Вильмонт Екатерина Николаевна (Астрель, 2012)
Экземпляры: ф.6 (20131024) / Инвентарный номер: 55171 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44